Soft-bottom benthic assemblage changes due to tropical seasonal upwelling (Bahía Salinas, Costa Rican Pacific) - Sibaja-Cordero, Jeffrey A.; Cortés, Jorge; Bogantes, Viktoria; Vargas, Rita; García–Mendez, Kimberly (Revista de Biología Tropical, 2025)
Introduction: Seasonal upwelling is a displacement offshore of surface seawater and replacement by cool deeper water with higher nutrient levels by the influence of the wind. On the north Pacific coast of Costa Rica the upwelling is present from December to April. Objective: Within this seasonal upwelling area, Salinas Bay was sampled to determine whether the upwelling has an effect on the diversity, composition, and trophic guilds of the soft-bottom benthic community. Methods: The bay was visited during the upwelling and non-upwelling seasons of 2007-2009. A number of 6 to 9 grab samples were taken in each sampling event. Results: Richness and abundance were lower in the non–upwelling season and the highest values were observed at the end of the upwelling. The taxa composition of assemblages varied partially across the seasons, depending on the upwelling intensity. Conclusions: The species composition was more diverse and abundant at the end of the upwelling season than at the start or in the non–upwelling season. Differences in infaunal assemblages during the seasonal upwelling could be explained by the change in characteristics of the sediment-water interface, nutrients, and sediment movements that promote the increase of planktonic productivity, and thus food availability.